THE DEMARGINALIZATION OF FEMALE DISCOURSES: ON THE INTERSECTIONAL DISCRIMINATIONS AGAINST WOMEN IN THE HELP - HUNG-CHANG LIAO; YA-HUEI WANG (LINGUISTICA, 2024)
This paper aimed to examine the unfair treatment and inequality among women by using and assessing the racial, class, and gender perspectives. It also demonstrated the intersectional discrimination against women, and how it brought the oppression and subordination of women in the private and public spheres, which can be characterized as violations of basic human rights and obstacles to the attainment of women’s equality, development, and integrity. In order to further demonstrate the intersectional discrimination against women, the researchers took The Help as a case study to compare various oppressive situations of White middle-class and African-American women and depict how the multiple and overlapped forms of oppression and structural discrimination should be taken into consideration to address the intersectional discriminations against women, particularly African American women. This study adopted latent-content analysis, including primary and secondary resources, as a qualitative method to facilitate analysis of underlying content. The study further concentrated on the diverse perspectives of women to observe various forms of discrimination and examine how the intersectionality of race, class, and gender affects their experiences and conditions of being discriminated. While reflecting upon the discrimination and oppression of the underprivileged genders, races and social classes, readers may manage to deconstruct the “intersectionality” and better empathize with those who are marginalized.